Service Reliability in a Network Context: Impacts of Synchronizing Schedules in Long Headway Services. Issue 1 (January 2014) - Lee, Aaron; van Oort, Neils; van Nes, Rob
This paper presents research on synchronization of transfers and its impact on service reliability from a passenger perspective. Passenger reliability was analyzed for the case of a multioperator transfer node. A method was developed to calculate the passenger-centered reliability indicators, additional travel time, and reliability buffer time, by using scheduled and actual vehicle arrival and departure times as inputs. Five major factors were identified as affecting reliability at a particular transfer: scheduled transfer time, distributions of actual arrivals of the first and second line, headways, transfer walking time, and transfer demand. The method was demonstrated in a real network case, in which changing a specific transfer had effects on other transfers from the transfer point. This method can be applied in a cost-benefit analysis to identify the benefits and costs of reliability for different groups of passengers, thereby supporting proper decision making.